Lettuce weed control with prior soil solarization - Pereira, Larissa [UNESP]; Tejada, Jorge Luis [UNESP]; Filho, Arthur Bernardes Cecílio [UNESP]; Da Costa Aguiar Alves, Pedro Luís [UNESP] (Lepidus Tecnologia, 2023)
Lettuce is a leafy crop appreciated for the supply of nutrients that favor the immune system. However, like other crops, it is subject to weed interference. Due to its low competitiveness and the impacts of herbicides, it is necessary to search new ways to control weeds. This work aims to determine the effects of solarization on weed control and on the productivity of 'Verônica' lettuce with or without soil revolving after solarization. The experimental design was randomized blocks in a factorial scheme 7x2 with four replications. The beds were weeded, irrigated and covered with 150 μm thick transparent polyethylene in different periods (first factor): five solarization periods (75, 60, 45, 30, and 15 days with solarization) and two controls (without and with weeds), with or without soil revolving (second factor). Weed phytosociology (frequency, density and relative dominance, importance value index, and relative importance) and lettuce productivity were evaluated. The control of the weed community (with a predominance of Cyperus rotundus, Eleusine indica and Digitaria spp.) with solarization was not efficient. However, the non-revolving treatment decreases the density of some weeds and positively affects the productivity and commercial characteristics of lettuce.
Keywords: Lactuca sativa L.; Physical weed control; Plastic film covers